DOUBLE GALAXIES AND THE DARK MATTER - Shakenov, M.B.; Chechin, L.M. (Recent Contributions to Physics, 2018)
Physical, possibly physical, possibly optical and optical pairs of the catalogue of double galaxies are determined through statistical criteria. Existence of the dark matter in double galaxies and projection effect to results of observing are also discussed.